The study of causes, mode of delivery in intrauterine fetal death and associated complications - Deshpande, Radhika S.; R., Manvi M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Intra uterine fetal death (IUFD) is defined as the baby born with no signs of life at or after 28 weeks of gestation. It is important to diagnose the cause in order to avoid further recurrence and to treat any maternal associated factors. The aim of the present study was to calculate incidence of IUFD in our hospital and know the causes, mode of delivery, associated complications. So we can take measures to prevent them in future. Methods: The retrospective study was conducted in the department of Obstetrics and Gynecology in Kanachur Medical College, Mangalore from January 2017 to January 2020. The women with confirmed diagnosis of IUFD on Ultrasound and beyond 28 weeks of gestation were included in the study. Results: In the study period, total 2026 patients delivered, of which 40 cases were IUFD, hence our incidence rate was 19.74 per 1000 population. 62.5% cases were multigravida. 15% had previous history of abortions while 5% previously had IUFD. In 37.5% cases, the cause was unknown, followed by 22.5% having pregnancy induced hypertension. Anemia contributed to 17.5% and placental causes in 12.5%. 10% of the women had PPH. One patient had sepsis, followed by acute renal failure and later died of multi organ failure. Conclusions: All the causes are not preventable, many of them can be identified early in pregnancy and thus IUFD can be prevented. All the high risk pregnancies should undergo antenatal fetal surveillance and should have frequent ante natal visits to reduce IUFD rates.